Synthesis and Biological Evaluation of Novel Benzothiazepines As Potential Antifungal, Anti-Tubercular and Cytotoxic Agents - Rao, J. Subba; Chandra, S. Ravi; Chakravarthy, A.; Yazdan, Sk. Khadar; Rani, V. Jhansi; Kumar, B. Praveen (Journal of Neonatal Surgery, 2025)
The present study describes the synthesis and biological activity of chalcone based 1,5-benzothiazepine derivatives from3,4-dichloroacetophenone by condensation with 2-aminothiophenol. The chemical characterization data of 1,5-benzothiazepine derivatives was done by elemental analysis, IR, 1H NMR, 13C NMR, and mass spectral methods. The results of the biological evaluation of synthesized compounds for their preliminary antifungal, antitubercular, and cytotoxic activities are included. The antifungal activity of 1,5-benzothiazepines was greater for benzothiazepine scaffolds, which are much more required for the activity. Most of the compounds were nearly equipotent against both the fungal species Aspergillus niger and Candida tropicalis. However, compound o, containing a 2"-thienyl ring present at the 5th position of the pyrazoline scaffold, was the most potent, with a MIC of 1 µg/mL. The compounds h and m containing 4”-trifluorophenyl and 2”-furyl scaffolds were next in activity against both Aspergillus niger and Candida tropicalis with MICs of 2 µg/mL. Most of the othercompounds were also active against both the fungal strains at MIC 4–16 µg/mL, respectively. The cytotoxicity of the 1,5-benzothiazepines was found to be greater for the compound o (MIC = 2 µg/mL) containing a 2”-thienyl ring at the 2nd position of the benzothiazepine scaffold, which was found to be more potent than the standard cytotoxic